Uniformed service officers’ age as a variable differentiating the perception of counterproductive work behaviors - Szeliga-Duchnowska , Anna; Szewczyk, Mirosława (Kultura-Społeczeństwo-Edukacja, 2018)
Szeliga-Duchnowska Anna, Szewczyk Mirosława, Uniformed service officers’ age as a variable differentiating the perception of counterproductive work behaviors. „Kultura – Społeczeństwo – Edukacja” nr 2(14) 2018, Poznań 2018, pp. 205–219, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.15. At the foundation of this research lies the belief that the age can directly differentiate the perception of counterproductive work behaviors. The aim of the article is to identify and present the relationship between age and the perception of counterproductive work behaviors. The survey research was carried out in June 2017, with the use of Internet-based survey questionnaire (CAWI). There were altogether 198 officers examined. The results confirm the existence of variety counterproductive behaviors according to the classification proposed by P.E. Spector. The analysis results confirm the appearance of dependence between the age of officers and their perception of counterproductive behaviors. The conclusions which come from the research can have significant implications to superiors in the scope of prophylactic actions aimed against counterproductive behaviors.